Trends in food product innovations and the level of economic development - Szczepan Figiel; Justyna Kufel-Gajda (Economic and Environmental Studies (E&ES), 2017)
Existence of relationships between consumption viewed from quantitative as well as qualitative standpoint and level of economic development seems obvious. However, both food perception and food choices depend not only on the level of economic development, but they are also driven by innovative actions of food producers. The purpose of this paper was to analyse how current trends in food product innovations are related to the levels of national incomes in selected countries. An empirical analysis was performed using data on 15 food product innovation trends provided by XTC World Innovation Panorama, and the World Bank data on the GNI levels. It was shown that the level of economic development determines the direction of food innovations and related quality of food consumption. It leads to a conclusion that after reaching a certain threshold income, demand for the food quantity consumed becomes substituted with demand for food quality attributes.
Keywords: O57; F63; M37; 330; innovation trends; food products; national incomes